Comparação do isolamento microbiológico e da reação em cadeia da polimerase no diagnóstico de salmonelose em bezerros infectados experimentalmente com Salmonella Typhimurium - Silva, D. G. [UNESP]; Ávila, L. G. [UNESP]; Berg, R. [UNESP]; Silva, D. R. [UNESP]; Conde, S. O. [UNESP]; Lemos, M. V. F. [UNESP]; Fagliari, J. J. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
The efficiency of microbiological culture and polymerase chain reaction (PCR) for detection of Salmonella Typhimurium is compared in fecal samples of Holstein calves experimentally infected with 10(9) CFU of Salmonella Typhimurium. Seventy-two fecal samples were analyzed by microbiological culture and PCR associated with selenite cystine (SC) and Muller-Kauffmann tethrationate (TMK) selective enrichment broths. Regardless of the selective enrichment broth, the microbiological culture was significantly better than PCR for detection of positive samples of Salmonella Typhimurium. The selective enrichment broths SC and TMK had no effect on the efficiency of the microbiological culture. The SC broth was the best option as selective enrichment associated to PCR.
Comparison of microbiological culture and polymerase chain reaction in the diagnosis of salmonellosis in Salmonella Typhimurium-infected calves
Keywords: Cattle; feces; bacteriological isolation; Salmonella Typhimurium; Bovino; Fezes; isolamento bacteriano; Salmonella typhimurium